Boundedness of p-Adic Singular Integrals and Multilinear Commutator on Morrey-Herz Spaces - Yanlong Shi; Li Li; Zhonghua Shen (Journal of Function Spaces)
In this paper, we establish the boundedness of classical p-adic singular integrals on Morrey-Herz spaces, as well as the boundedness of multilinear commutator generated by p-adic singular integral operators and Lipschitz functions or by p-adic singular integral operators and λ-central BMO functions.